Analysis of Ocular Injury Characteristics in Survivors of the 8.12 Tianjin Port Explosion, China - Hao Jiang; Chao Xue; Yanlin Gao; Yan Wang (Journal of Ophthalmology)
Introduction. On the evening of August 12, 2015, a large chemical explosion occurred at Tianjin Port. We analyzed ocular injury characteristics in the survivors of this accident. Methods. Twenty injured eyes of 17 hospitalized patients were included. Initial best-corrected visual acuity (BCVA), injury type, injury cause, relative afferent pupillary defect (RAPD), zone of injury (ZOI), and ocular trauma score (OTS) were evaluated. Final BCVA and enucleation were the final outcome index. The relationship between risk factors and final outcomes was analyzed. Results. The patients comprised 14 males and 3 females (mean age, 35.24 ± 12.68 years). Eighteen eyes had open-globe and 2 had closed-globe injuries. Fifteen ocular injury types were reported. Initial visual acuity (VA) was 20/50 to 20/200, 20/200 to finger counting (FC), hand motion to light perception (HM-LP), and no light perception (NLP) in 2, 7, 7, and 4 eyes, respectively. RAPD was found in 5 eyes. Most eyes sustained severe injuries with OTSs of 1 (25%) and 2 (40%). Of the injured eyes, 50% had Zone III injuries. In 95% of the injured eyes, glass was the cause of injury. Three of 4 eyes with an initial VA of NLP had a final VA of NLP and an outcome of enucleation. In 5 eyes with RAPD, 3 had a final VA of NLP and a final outcome of enucleation. Eyes with lower OTSs generally had poorer outcomes. All eyes with a final VA of NLP and an enucleation outcome had Zone III injuries. All 3 eyes with an enucleation outcome had retinal injuries, whereas eyes with no retinal injury had a better final BCVA. Conclusions. Explosions can inflict severe ocular trauma, even indoors; 90% of injured eyes had open-globe injuries caused by glass fragments. Initial NLP, RAPD, low OTS, posterior extended wound, and retinal injury indicate a poor final outcome.